2020
DOI: 10.1021/acsaem.0c00795
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Fe–Li, Ni–Li Antisite Defects in LiFePO4 and LiNi1/3Co1/3Mn1/3O2 by Optimized Synthesis Methods

Abstract: Antisite defects in LiFePO 4 and LiNi 1/3 Co 1/3 Mn 1/3 O 2 cathode materials will severely decrease Li + diffusion ability and the cell capacity. However, the mechanism of constraining antisite defects during the hydrothermal route is not fully understood. Herein, the Fe−Li, Ni−Li antisite defects in LiFePO 4 and LiNi 1/3 Co 1/3 Mn 1/3 O 2 cathode materials are successfully suppressed by optimized synthesis methods. As a result, their discharge capacity and rate performance at room and low temperature are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Furthermore, the enlarged interplanar spacing facilitates the transport of Li + for less diffusion resistance. The modification of LC-LFP by adding La and Ce favors the construction of a regular crystal with less Fe–Li anti-site defects as shown in FTIR spectroscopy (Figure e) due to a closer wavenumber of LC-LFP (957.7 cm –1 ) to the Fe–Li defect-free theoretical value (957.0 cm –1 ) . As a result, the prepared LC-LFP would obtain an enhanced electrochemical performance.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the enlarged interplanar spacing facilitates the transport of Li + for less diffusion resistance. The modification of LC-LFP by adding La and Ce favors the construction of a regular crystal with less Fe–Li anti-site defects as shown in FTIR spectroscopy (Figure e) due to a closer wavenumber of LC-LFP (957.7 cm –1 ) to the Fe–Li defect-free theoretical value (957.0 cm –1 ) . As a result, the prepared LC-LFP would obtain an enhanced electrochemical performance.…”
Section: Resultsmentioning
confidence: 90%
“…The LiFePO 4 cathode (LFP) exhibiting favorable electrochemical potential, cost saving, and high stability has been widely employed in lithium-ion batteries (LIBs) for large-scale energy backup systems and electric vehicles (EVs). Unfortunately, its poor electrical conductivity (10 –9 –10 –10 S cm –1 ) and sluggish lithium ion diffusion kinetics (∼10 –14 cm 2 s –1 ) deriving from the covalent character of polyanion frameworks are inhibiting the raise of charging/discharging rates in LiFePO 4 -based LIBs . To address these issues, two promising approaches, reducing particle size to a nanoscale and carbon coating on the active particles, are usually adopted to enhance the electrochemical performance. , Nevertheless, these strategies are still not satisfying the requirement of the application on the ultra-high rate (>50 C) and larger power density due to the limited improvement of Li + deintercalation kinetics …”
Section: Introductionmentioning
confidence: 99%
“…Antisite defects can directly change the chemical environment of the defective region, impeding ion diffusion and deteriorating battery performance in most cases. , The impeded ion diffusion can be attributed to two reasons: (1) antisite defects act as obstructions along the ion diffusion pathways; (2) antisite defects cause lattice shrinkage and thus increase ionic diffusion energy barriers . OVs are intrinsic defects in many battery materials, and their presence can dramatically alter the chemical and mechanical stability of battery materials.…”
Section: Impact On Electrochemical Performancementioning
confidence: 99%
“…[9,[25][26][27] Previous studies indicated that LiFePO 4 synthesized at a low temperature has about 5~10 % LiÀ Fe anti-sites, which will decrease after high-temperature treatment. [28] Various methods have been used to reduce the defect concentration, such as lithium-excess, [9] enlarging exposure face, [29] suppressing the prior occupancy of Fe ion, [30] controlling the nucleation and evolution, [31] regulating pH values, [32] reducing the particle size, [16] etc. Whether there is any correlation between the LiÀ Fe anti-site and the memory effect of LiFePO 4 ?…”
Section: Introductionmentioning
confidence: 99%